Catotrichinae (Diptera: Cecidomyiidae) in Tasmania, with the description of Trichotoca edentula gen. et sp. n. - Jaschhof, Mathias; Jaschhof, Catrin (Zootaxa, 2008)
Two species of catotrichine gall midges are shown to occur in Tasmania: Trichotoca edentula sp. n. and Trichotoca fraterna (Jaschhof) comb. n., the latter known previously from the Australian mainland. A new genus, Trichotoca, is founded to receive these two species and is shown to be sister-group of Catotricha Edwards, the genus now comprising all the extant catotrichine species in the northern hemisphere. Another new genus, †Mesotrichoca, is founded for the only known fossil catotrichine, †Catotricha mesozoica Kovalev. Adult morphology of the Catotrichinae is revised and briefly discussed.